Perfil epidemiológico de portadores do HIV com manifestações estomatológicas em cinco centros de referência na cidade de Porto Alegre - Petruzzi, Maria Noel Marzano Rodrigues (2012)
Since the beginning of AIDS epidemic many efforts have been employed to define the value of oral cavity lesions as clinical markers of this disease. However, there are fewer reports on oral pathologies from developing countries. The main purpose of this study was to describe the epidemiological characteristics of HIV-positive adults carriers of associated oral lesions and evaluate the risk factors for the occurrence of these affections. For that purpose, a cross-sectional, retrospective and descriptive-analytical study was conducted in medical/dental charts of 534 patients at 5 Referral Centers for HIV/AIDS management in Porto Alegre city, Rio Grande do Sul, Brazil. Data analysis consisted of cross-tabulations, binomial t test, and logistic regression models. Nearly 52% of patients were men, 88.2% were older than 30 years and 78.1% progressed to AIDS in less than 5 years after HIV diagnosis. The unemployment index was 35% and was significantly more common among men (p<0.001). Approximately 60% of the patients used highly active antiretroviral therapy. Tuberculosis was the AIDS-defining disease most commonly seen (18.5%).The oral manifestations were seen in 19.3% of patients at the time of HIV diagnosis. Oral candidiasis was the most prevalent lesion in the oral cavity (50%), denoting predilection by the female gender (p=0.031). The risk factors for the occurrence of this affection were moderate (p<0.009) and severe (p<0.001) immunologic impairment and alcoholism (p=0.011). CD4+ counts below 500 cells/mm³ (p=0.029), a viral load above 5000 copies/mm³ (p=0.003) and smoking (p=0.005), contributed for hairy leukoplakya occurrence. The advanced stage of the disease and rapid progression to AIDS observed in this sample requires health professionals attention, since they may be indicative of diagnosis and treatment delay. Dentists and other health professionals might be aware to the onset of oral manifestations, since these lesions were helpful markers for the detection of HIV and suggestive clinical signs of immune deterioration and disease progression in the current survey.